Interpretation of vaginal metagenomic characteristics in different types of vaginitis - Jiarong Song; Xue Dong; Yue Lan; Yunwei Lu; Xu Liu; Xuena Kang; Zhonglu Huang; Bisong Yue; Yu Liu; Wenjin Ma; Libo Zhang; Haijun Yan; et al. (mSystems, 2024)
ABSTRACTAlthough vaginitis is closely related to vaginal microecology in females, the precise composition and functional potential of different types of vaginitis remain unclear. Here, metagenomic sequencing was applied to analyze the vaginal flora in patients with various forms of vaginitis, including cases with a clue cell proportion ranging from 1% to 20% (Clue1_20), bacterial vaginitis (BV), vulvovaginal candidiasis (VVC), and BV combined with VVC (VVC_BV). Our results identified Prevotella as an important biomarker between BV and Clue1_20. Moreover, a gradual decrease was observed in the relative abundance of shikimic acid metabolism associated with bacteria producing indole as well as a decline in the abundance of Gardnerella vaginalis in patients with BV, Clue1_20, and healthy women. Interestingly, the vaginal flora of patients in the VVC_BV group exhibited structural similarities to that of the VVC group, and its potentially functional characteristics resembled those of the BV and VVC groups. Finally, Lactobacillus crispatus was found in high abundance in healthy samples, greatly contributing to the stability of the vaginal environment. For the further study of L. crispatus, we isolated five strains of L. crispatus from healthy samples and evaluated their capacity to inhibit G. vaginalis biofilms and produce lactic acid in vitro to select the potential probiotic candidate for improving vaginitis in future clinical studies. Overall, we successfully identified bacterial biomarkers of different vaginitis and characterized the dynamic shifts in vaginal flora between patients with BV and healthy females. This research advances our understanding and holds great promise in enhancing clinical approaches for the treatment of vaginitis.IMPORTANCEVaginitis is one of the most common gynecological diseases, mostly caused by infections of pathogens such as Candida albicans and Gardnerella vaginalis. In recent years, it has been found that the stability of the vaginal flora plays an important role in vaginitis. Furthermore, the abundant Lactobacillus-producing rich lactic acid in the vagina provides a healthy acidic environment such as Lactobacillus crispatus. The metabolites of Lactobacillus can inhibit the colonization of pathogens. Here, we collected the vaginal samples of patients with bacterial vaginitis (BV), vulvovaginal candidiasis (VVC), and BV combined with VVC to discover the differences and relationships among the different kinds of vaginitis by metagenomic sequencing. Furthermore, because of the importance of L. crispatus in promoting vaginal health, we isolated multiple strains from vaginal samples of healthy females and chose the most promising strain with potential probiotic benefits to provide clinical implications for treatment strategies.